Comparative Study on the Establishment of a Personal Data Supervisory Commission between Indonesia and the United Kingdom - Alendra Nauval Mufti Rayhan; Karisma Anggraeni Wijaya; Akhmad Mauladani Firmansyah (Universitas Airlangga, 2025)
The Industrial Revolution 4.0 has transformed patterns of social interaction, shifting from conventional practices to digital forms of engagement in daily life. This transformation underscores the urgent need for supervisory institutions to safeguard personal data in the digital sphere. This paper examines the establishment of a personal data supervisory authority in Indonesia by comparing it with the United Kingdom, which has developed a well-established personal data protection authority. Employing normative legal research with a comparative and statutory approach, the study finds that the acceleration of digitalization has intensified the demand for robust data protection mechanisms. The analysis highlights the relevance of Indonesia’s Personal Data Protection Law, read in light of comparative experience with the UK’s regulatory authority. The findings suggest that the institutional design of Indonesia’s supervisory body should be adapted to national needs while reflecting international best practices.